Argilominerais de Coberturas Sedimentares Cenozóicas do Centro-leste do Estado de São Paulo - De Melo, Mário Sérgio; Brandt Neto, Max [UNESP]; Coimbra, Armando Márcio; De Moraes, Maria Cristina; De Sant'anna Taddeo, Jairo; Cuchierato, Gláucia (My University, 1997)
Clay mineral analysis contributed to the mineralogical characterization and stratigraphic setting of continental Cenozoic deposits of central-eastern portion of São Paulo State, southeastern Brazil. These deposits, often thin and discontinuous, comprise the Itaqueri Formation (Cretaceous-Paleogene), Rio Claro Formation (Pliocene) and associated Neocenozoic deposits. X-ray diffractometry provided mineralogical and semiquantitative constitution of clays, while scanning electron microscopy (SEM) provided details about mineralogical constitution, packing of microscopic grains and nature (detrital or diagenetic) of clays. These results supported interpretations about paleoenvironmental conditions during sedimentation, revealing possible links between changing climates (dry or humid) and correlative Cenozoic deposits in southeastern Brazil. In addition, SEM images showed microstructures which influence on geotechnical behaviour (erosion and collapse phenomena) of sedimentary materials.
Keywords: Cenozoic; Cenozoic covers; Clay minerals